2017
DOI: 10.1371/journal.pone.0178893
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between white matter microstructure and executive functions suggests early developmental influence on long fibre tracts in preterm born adolescents

Abstract: Main objectivesExecutive functions are frequently a weakness in children born preterm. We examined associations of executive functions and general cognitive abilities with brain structure in preterm born adolescents who were born with appropriate weight for gestational age and who have no radiological signs of preterm brain injury on neuroimaging.MethodsThe Stockholm Neonatal Project (SNP) is a longitudinal, population-based study of children born preterm (<36 weeks of gestation) with very low birth weight (<1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 46 publications
(53 reference statements)
5
40
5
Order By: Relevance
“…We observed multiple, partially independent contributions of specific tracts to individual differences in gc and gf. The clearest associations were observed for the anterior thalamic radiations, cingulum, forceps major, forceps minor, and superior longitudinal fasciculus, all of which have been implicated to play a role in cognitive functioning in childhood and adolescence Navas-Sánchez et al, 2014;Peters et al, 2014;Tamnes et al, 2010;Urger et al, 2015;Vollmer et al, 2017). However, except for the superior longitudinal fasciculus, these tracts were not significant in NKI Rockland sample.…”
Section: Summary Of Findingsmentioning
confidence: 90%
“…We observed multiple, partially independent contributions of specific tracts to individual differences in gc and gf. The clearest associations were observed for the anterior thalamic radiations, cingulum, forceps major, forceps minor, and superior longitudinal fasciculus, all of which have been implicated to play a role in cognitive functioning in childhood and adolescence Navas-Sánchez et al, 2014;Peters et al, 2014;Tamnes et al, 2010;Urger et al, 2015;Vollmer et al, 2017). However, except for the superior longitudinal fasciculus, these tracts were not significant in NKI Rockland sample.…”
Section: Summary Of Findingsmentioning
confidence: 90%
“…Deficits in executive function have been identified in school‐age children born very preterm and these have involved goal‐directed behaviour, self‐regulation of emotions and working memory. Population‐based studies of children born preterm without radiological signs of perinatal brain injury have showed that alterations in regional brain tissue and microstructure in adolescence were associated with measures of executive functions and cognitive abilities .…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, for moderate-late ex-preterm children many cohort studies have identified a 1-2 fold increased risk for requiring special education or repeating a grade at ages 5-10 (Huddy et al, 2001;van Baar et al, 2009;Morse et al, 2009;Gurka et al, 2010). The development of these disorders and school-related difficulties can manifest in moderate-late expreterm children who had no gross neuroanatomical injury in the newborn period (Vicari et al, 2004;Vollmer et al, 2017); thus, absence of significant injury is not necessarily an indicator of later neurodevelopmental function and wellbeing. The posterior lobe of the cerebellum is interconnected with the prefrontal cortex, association cortices, and the limbic system, which allows for its involvement in higher executive functioning (Stoodley and Schmahmann, 2010;Stoodley, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Decreases in the white matter volumes of regions often impacted by preterm birth, such as the hippocampus and cerebellum (Rees and Inder, 2005;Rees et al, 2008;Volpe, 2003), are suggested to play a key role in the defects in neurodevelopment and behaviour following preterm birth (Counsell et al, 2003). In cases of moderate-late preterm birth, often the type of neuroanatomical injury is a subtle and diffuse delay in myelination compared to more marked decreases in brain volume seen in those born at lesser gestational ages (Vollmer et al, 2017;Volpe, 2003) when large-scale increases in brain structures are occurring. The cerebellum and hippocampus are particularly vulnerable to damage and developmental delay following preterm birth as they each continue to mature throughout late gestation (Rees and Inder, 2005;Rees et al, 2008;Rivkin, 1997;Volpe, 2008;Arnold and Trojanowski, 1996), and this trajectory of maturation is inevitably altered following preterm birth.…”
Section: Introductionmentioning
confidence: 99%